Predicting 3‐month risk for adolescent suicide attempts among pediatric emergency department patients. (21st July 2019) - King, Cheryl A.; Grupp‐Phelan, Jacqueline; Brent, David; Dean, J. Michael; Webb, Michael; Bridge, Jeffrey A.; Spirito, Anthony; Chernick, Lauren S.; Mahabee‐Gittens, E. Melinda; Mistry, Rakesh D.; Rea, Margaret; Keller, Allison; et al.
Abstract : Background: The incidence of adolescent suicide is rising in the United States, yet we have limited information regarding short‐term prediction of suicide attempts. Our aim was to identify predictors of suicide attempts within 3‐months of an emergency department (ED) visit. Methods: Adolescents, ages 12–17, seeking health care at 13 pediatric EDs (Pediatric Emergency Care Applied Research Network) and one Indian Health Service Hospital in the United States were consecutively recruited. Among 10, 664 approached patients, 6, 448 (60%) were enrolled and completed a suicide risk survey. A subset of participants ( n = 2, 897) was assigned to a 3‐month telephone follow‐up, and 2, 104 participants completed this follow‐up (73% retention). Our primary outcome was a suicide attempt between the ED visit and 3‐month follow‐up. Results: One hundred four adolescents (4.9%) made a suicide attempt between enrollment and 3‐month follow‐up. A large number of baseline predictors of suicide attempt were identified in bivariate analyses. The final multivariable model for the full sample included the presence of suicidal ideation during the past week, lifetime severity of suicidal ideation, lifetime history of suicidal behavior, and school connectedness. For the subgroup of adolescents who did not report recent suicidal ideation at baseline, the final model included only lifetime severity of suicidal ideation and social connectedness. Among males, the final model included only lifetime severity of suicidal ideation and past week suicidal ideation. For females, the final model included past week suicidal ideation, lifetime severity of suicidal ideation, number of past‐year nonsuicidal self‐injury (NSSI) incidents, and social connectedness. Conclusions: Results indicate that the key risk factors for adolescent suicide attempts differ for subgroups of adolescents defined by sex and whether or not they report recent suicidal thoughts. Results also point to the importance of school and social connectedness as protective factors against suicide attempts.